2000
DOI: 10.1161/01.hyp.36.3.371
|View full text |Cite
|
Sign up to set email alerts
|

β 2 -Adrenoceptor Polymorphism Determines Vascular Reactivity in Humans

Abstract: Abstract-Altered ␤-adrenergic regulation has been reported in individuals with hypertension. The variability in vascular responsiveness to ␤-agonists, such as isoproterenol, observed in humans may be explained partially by ␤ 2 -adrenoceptor polymorphism. Individuals with the Gln27 form of the receptor may show reduced vascular reactivity because of downregulation expression of the receptor in the vasculature. We screened 127 normotensive white subjects, 37 of whom were homozygous for these alleles. Thirty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
93
3
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 19 publications
12
93
3
3
Order By: Relevance
“…Stimulation of b 2 ARs in the vasculature results in vasodilation. 1 Several polymorphisms have been described in the gene for the b 2 AR. The A46G and the C79G polymorphisms are common polymorphisms and both result in amino-acid substitutions of the b 2 ARs, Arg16Gly and Gln27Glu, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of b 2 ARs in the vasculature results in vasodilation. 1 Several polymorphisms have been described in the gene for the b 2 AR. The A46G and the C79G polymorphisms are common polymorphisms and both result in amino-acid substitutions of the b 2 ARs, Arg16Gly and Gln27Glu, respectively.…”
mentioning
confidence: 99%
“…The positions are located in the amino terminus of the receptor and seem to influence the degree of downregulation of the receptor, 2 which may affect vascular reactivity. 1 b 2 AR polymorphisms have been associated with increased risk for cardiovascular disease through intermediate end points such as body mass index (BMI), 3 hypertension, 3,4 prevalence of diabetes mellitus type II. 4 Polymorphisms in the gene for the b 2 AR have also been reported to be associated with excess coronary events.…”
mentioning
confidence: 99%
“…As the functional implications of the Arg16Gly and Gln27Glu polymorphisms were revealed in vitro, their effects on the agonist-induced vasodilator response have also been investigated in vivo, and the results were controversial. 19,[20][21][22][23] Moreover, there was also no significant association detected between the blood pressure response to hydrochlorothiazide or atenolol and the Arg16Gly polymorphism in several studies. 24,25 An attenuation of b-adrenergic function and a potentiation of a-adrenergic function in cardiovascular tissues have been shown in hypertensive patients, suggesting the development of a postsynaptic a1 function dominance during the development and evolution of hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…19 The effect of these genotypes on receptor responsiveness, desensitization and downregulation has been investigated in vivo. Vascular responsiveness (forearm blood flow and hand vein dilation) to ADRB2 agonists 20,21 and mental stress or exercise 22 appears to be higher among Glu27 homozygotes in experimental situations involving healthy adult volunteers. Studies using the same agonist have also found higher responsiveness among Gly16 homozygotes versus Arg16 homozygotes or heterozygotes 20,23 although not uniformly.…”
Section: Introductionmentioning
confidence: 87%
“…Vascular responsiveness (forearm blood flow and hand vein dilation) to ADRB2 agonists 20,21 and mental stress or exercise 22 appears to be higher among Glu27 homozygotes in experimental situations involving healthy adult volunteers. Studies using the same agonist have also found higher responsiveness among Gly16 homozygotes versus Arg16 homozygotes or heterozygotes 20,23 although not uniformly. 21 Additionally, Gly16 homozygotes were resistant to desensitization of vascular response (regardless of position 27 amino acid), 21 and showed delayed onset, in the short term, of desensitization of cardiac response 24 and of downregulation of lymphocyte receptor density.…”
Section: Introductionmentioning
confidence: 87%